DO AGREGADO AO DESAGREGADO: MODIFICAÇÕES NA PAISAGEM DO FAXINAL LAJEADO DOS MELLOS, RIO AZUL\PR (1970-2016) - Kroin, Leonardo (2020)
Our dissertation discusses the transformations that took place in the landscape of Faxinal Lajeado dos Mellos, municipality of Rio Azul-PR, intensified from 1970 when agricultural mechanization began, with the appearance and use of the tractor and the insertion of crops, such as tobacco. This boosted the processes of disarticulation and disintegration in it, ever since altering elements of its landscape, leading to the reduction and replacement of native forest, changes in the structure of fences and in the growth of individual fences, called “closures”. This has been shown to be more accelerated in recent years, as the closures have increased, as well as the monocultures of soy, pine, eucalyptus and tobacco. To understand how these processes of disarticulation and disaggregation act and modify the natural and cultural aspects of Faxinal, significantly altering its landscape, we will start from the assumption that landscape is not what is seen, only, but what is built, destroyed and felt, to wit, they are cultural realities perceived through representations, values and points of orientation that are from a cultural and non-scientific nature (LATARJET apud GALANO, 2000, p. 85). Therefore, to think about this problem, we use the concepts of “landscape-mosaic” and “landscape-power”, Schörner (2016). Such concepts help us think through photographs and interviews, that we have produced over these two years in which we have accompanied the Faxinal Lajeado dos Mellos, the changes in its landscape, something that enabled us to observe, what are the effects and causes that such processes end up causing in the configuration of their landscape and how these transformations interfere respectively in the relations performed among faxinalenses about the common space, their collectivity and shared solidarity with the other members of the community. Thus, the new changes in the typology of fences, gates and the increase of closures, characterize the reflection of these changes in the relationship between these subjects and with the space of common use, something witnessed in the landscape. On the other hand, they also gain a new symbolism and meaning in Faxinal, of privatization and individualization of natural resources and common spaces.